(untitled) (LACCEI, 2024)
The recognition tests of the structural, chemical, superficial and morphological characteristics of the adsorbents is a key point to take into account when the use of these materials is proposed as filling in adsorption columns for the treatment of industrial effluents. The superficial microanalysis of the material by SEM-EDS allows to study the pattern of distribution of the contaminants and to identify the possible functional groups participating in the adsorptive process. In this work, preferential adsorption zones have been found due to heterogeneities and the presence of organic groups on the surface of the material made up of marine algae with different affinities for each of the adsorbates tested (metal ions).